2021
DOI: 10.1155/2021/6036891
|View full text |Cite
|
Sign up to set email alerts
|

How Much PEEP Does High Flow Deliver via Tracheostomy? A Literature Review and Benchtop Experiment

Abstract: Background. High flow tracheostomy (HFT) is a commonly used weaning and humidification strategy for tracheostomised patients, but little is known as to how much PEEP or mechanical benefit it offers. Patient anatomy and device characteristics differentiate it from high flow nasal cannula and the physiological effects observed. Objectives. (1) To review the available literature on the effects of HFT on airway pressure and indices of gas exchange. (2) To quantify PEEP generated by a HFT  circuit. Methods. A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A low, but potentially beneficial, CPAP effect has been found for HFT nasal cannula 22 . In comparison, the HFT‐T CPAP effect is modest, while still helpful during the weaning process 17,19 . The present study's benchtop experiments confirmed no or very little pressure support by HFT‐T‐OWV.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…A low, but potentially beneficial, CPAP effect has been found for HFT nasal cannula 22 . In comparison, the HFT‐T CPAP effect is modest, while still helpful during the weaning process 17,19 . The present study's benchtop experiments confirmed no or very little pressure support by HFT‐T‐OWV.…”
Section: Discussionmentioning
confidence: 45%
“…The absence of flow through the OWV and tracheostomy tube for maximum pressure measurements was confirmed by keeping the tracheostomy tube tip below the water surface of a filled container (Figure 2). If flow occurred, bubbles would be visible, and the tip of the tube moved deeper under water 19 . Pressure was measured after the adapter's side holes, before the OWV.…”
Section: Methodsmentioning
confidence: 99%
“…PEEP attained by high-flow oxygen therapy using a tracheostomy tube in tracheostomized patients has been shown to have various clinical benefits [ 8 , 35 ]. Although the relationship between the magnitude of EEP and inflow rates was previously investigated experimentally using high-flow tracheostomy [ 24 , 38 ], it was still unknown whether simple geometrical changes in tracheostomy tube connectors, including the stenosis rate and inlet angles, could potentially generate PEEP. Since it is thought that PEEP is a consequence of the balance between connector fluid flow and lung mechanical responses, the 3D CFD of airflow in the connector during respiration under boundary conditions will be useful to understand the mechanical conditions necessary for PEEP generation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HFNC can decrease the work of breathing and also enhance neuroventilatory drive [ 35 ]. More recently, benchtop experiments were performed with a high-flow tracheostomy circuit, and the so-called potential PEEP, defined as the blow-off pressure of the open gas delivery system, was approximately 0.3–0.9 cmH 2 O (≈ 29.4–88.3 Pa) for an inflow rate of 40–60 L/min [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…When comparing HFT delivered through a nasal cannula (nHFT) vs. via a tracheal interface (tHFT), tHFT seems to generate even less distending pressure. In a bench trial, Thomas et al demonstrated that tHFOT generates a potential PEEP of 0.3 cmH 2 O, 0.5 cmH 2 O, and 0.9 cmH 2 O when the flow is set to 40 L/m, 50 L/m, and 60 L/m, respectively [ 47 ]. In line with these findings, tHFOT produces lower tracheal mean and peak expiratory pressure when compared to nHFT [ 48 ].…”
Section: The Potential Mechanisms By Which Hhft May Offer Advantages ...mentioning
confidence: 99%